Pengembangan healthy snack bar kombinasi koro benguk (Mucuna pruriens l.) dan ubi jalar ungu (Ipomoea batatas l.) berdasarkan penerimaan konsumen - Cici Wahyuni; Affan Fajar Falah; Arita Dewi Nugrahini (Agroindustrial Technology, University of Trunojoyo Madura, 2026)
Market demand shows increasing consumer behavior toward healthy snack products, which are lower in sugar, salt, fat, and contain other nutrients. However, snack bars on the market contain high levels of sugar and fat. This research aims to develop a healthy snack bar formula based on koro benguk flour and purple sweet potato with stevia sweetener, and to comparative analysis of benchmark products based on healthy snack bar quality standards and product sensory quality. This study used a 2-factor Completely Randomized Design consisting of a variation of koro benguk and purple sweet potato flour: A1 (45: 55%), A2 (40: 60%), A3 (35: 65%) and the factor of adding stevia sweetener: B1 (1.5ml), B2 (3 ml), B3 (4.5 ml). Data analysis in this study used the Two Way ANOVA and Kruskall Wallis methods. The best formula based on consumer acceptance is sample A2B2 (40% koro benguk flour: 60% purple sweet potato flour: 3 ml stevia sweetener) with characteristics of moisture content 15.59%, ash 2.64%, fat 19.71%, protein 14.94%, carbohydrate 47.33%, total dietary fiber 4.77%, total sugar 9.95%, and salt 0.034%. The snack bar product has the advantage of being lower in sugar, salt, and fat content, but with fiber, protein, and a sensory quality preference score that is lower than the commercial product. Healthy snack bar products still need to be evaluated to improve product performance to commercial products.